Enhanced lithium storage performance of graphene nanoribbons doped with high content of nitrogen atoms. (18th March 2019) - Qian, Yuting; Jiang, Lai; Ullah, Zaka; Guan, Zhixing; Yu, Congcong; Zhu, Shoupu; Chen, Mingliang; Li, Weiwei; Li, Qi; Liu, Liwei
Abstract: Nitrogen doping can provide a large number of active sites for lithium-ion storage, thus can yield a higher capacity for lithium-ion batteries. However, most of the reported N-doped graphene-based materials have low nitrogen content (<10 wt%) as the introduction of nitrogen atoms prefer to be produced at edges and defects in the graphene lattices. Owing to the formation of edges and defects, the doped states or active sites can easily be located and nitrogen contents can be determined precisely. Here we present the preparation of N-doped graphene nanoribbons with high nitrogen contents (11.8 wt%) and a facile tunable configuration of doped states. The material can be used as an anode for lithium-ion batteries and shows a higher capacity (the electrode has a reversible capacity of 1100.34 mA h g −1 at a charge/discharge rate of 100 mA g −1, corresponds to a discharge time of about 9 h), better rate performance (the electrode has a reversible capacity of 471 mA h g −1 at the current density of 2 A g −1, corresponds to a discharge time of about 11.6 min) and improved cycling stability (87.37% of the initial capacity after 200 cycles). The experimental results and first-principle calculations suggest that the residual oxygen-containing functional groups of N-doped graphene nanoribbons promote the formation of pyrrolic nitrogen at edges and substantially increase the room for nitrogen doping. This work opens new strategies for designing and developing N-doped graphene anodes for high performance lithium-ion batteries.